PENERAPAN KNOWLEDGE MANAGEMENT SYSTEM BERBASIS WEB SEBAGAI SISTEM PENDUKUNG PENGAMBILAN KEPUTUSAN DALAM PENGURANGAN RISIKO BENCANA DI INDONESIA: Studi Kasus di Badan Nasional Penanggulangan Bencana (BNPB) - , Narwawi Pramudhiarta ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aims of this research is to implement a web based knowledge management system that able to manage, process, and analyze the disasters historical data in Indonesia. The disaster historical data will be used as useful knowledge to BNPB and other parties involved in the decision-making for disaster risk reduction. The knowledge management system provided a web-based media to BNPB and people who need the information and documents related to disaster management. The development of the web based knowledge management system in this study was using historical disaster events in Indonesian that has occurred for a period of 15 years (1997-2012) consist of time, location, type of disaster, number of casualties, damage and loss disaster. In addition to these data the other materials used were the documents related to disaster management ever undertaken by BNPB through activities that existed or from the disaster emergency response. There are two main menus in the system wiki and disaster historical data menu. The wiki menu developed using contains management system (CMS) from Drupal. Whereas, the development of the data is done by modifying the existing DesInventar system which is open source software in the form of concepts and methodologies in building database loss, damage, and other effects caused by the disaster. The results showed that the availability of data and information related to disaster management in BNPB used as input for the development of a knowledge management system in this study. One result of the utilization of knowledge management system that can be used in support of disaster risk reduction programs are disaster prone area indexes and disaster risk assessments are generated based on historical data of disasters, the vulnerability of the population, and data loss due to disasters in the past.